Representative candidate of gelatinase encoded gene in Enterobacter aerogenes (Strain EA1) for hydrolyzing porcine gelatin - Safiyyah Shahimi,; Sahilah Abd. Mutalib,; Rozida Mohd. Khalid,; Mohd Fadly Lamri,; Maaruf Abdul Ghani,; Mohd. Faizal Abu Bakar,; Mohd. Noor Mat Isa, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Enterobacter aerogenes (Strain EA1) was characterised as gelatinase species-specific bacterium to porcine and fish gelatin. This bacterium offers the possibility of enzymes production to each species gelatin. In this study, a bioinformatic analysis toward genome sequence of E. aerogenes was perfomed to determine genes encoded for gelatinase. E. aerogenes were partially genome sequenced resulting in 5.0 mega basepair total size of sequence. From pre-process pipeline, 78.58% of high quality reads was obtained for E. aerogenes. Genome assembly produced 120 contigs with 55.17% of GC base content. Protein prediction analysis determined 4705 genes from E. aerogenes. Two gelatinase candidate target genes selected from E. aerogenes were NODE_9_length_26866_cov_148.013245_12 containing 1029 bp sequence and NODE_24_length_155103_cov_177.082458_62 containing 717 bp sequence with highest similarity identity percentage against gelatinase enzyme available in Swiss-Prot and NCBI online database. Then, primers were designed for each target genes based on the open reading frame of selected genes. The expected gene candidate showed, 1029 bp and 717 bp amplicons for gen NODE_9_12 and gene NODE_24_62, respectively. Thus, gelatinase candidate encoded genes of E. aerogenes were identified for hydrolyzing porcine gelatin.